Fractional Exhaled Nitric Oxide Measurement in Pulmonary Hypertension: A Follow-Up Study. (April 2018) - Akbay, Nilay Orak; Bingol, Zuleyha; Kiyan, Esen; Karaayvaz, Ekrem Bilal; Bilge, Ahmet Kaya; Issever, Halim; Okumus, Gulfer
Pulmonary hypertension (PH) is a fatal disease although significant improvements in treatment are achieved. Easily implemented and noninvasive prognostic techniques are needed while following-up these patients. The aim was to investigate the role of fractional exhaled nitric oxide (FeNO) in follow-up for patients with PH. In this longitudinal study, patients with pulmonary arterial hypertension (PAH) and chronic thromboembolic PH (CTEPH) who were seen in PH Outpatient Clinic, Istanbul Faculty of Medicine, Istanbul University, were enrolled in the study. Echocardiography, 6-minute walking test, brain natriuretic peptide, and FeNO measurements were performed, and World Health Organization functional class was evaluated to all patients at baseline, and third, and sixth months. Right-heart catheterization and pulmonary function tests at the time of diagnosis were recorded. The study comprised 31 patients (23 women, 8 men; mean age: 53.4 ± 17.1 years) with PAH (n = 19) and CTEPH (n = 12) and 80 healthy controls. Patients with PH had lower FeNO values than the control group (16.5 ppb vs 19.8 ppb; P < .05). Fractional exhaled nitric oxide values did not change during follow-up and did not correlate with other follow-up measures except tricuspid annular plane systolic excursion values. Fractional exhaled nitric oxide was higher in the idiopathic PAH subgroup at baseline and at third month than patients with PAH associated with other diseases. Fractional exhaled nitric oxide did not change in patients who had clinical deterioration. As a conclusion; Patients with PH had lower FeNO values than healthy controls, but FeNO did not change significantly during follow-up. Large-scale studies with prolonged follow-up periods are needed to understand the role of FeNO in the follow-up of the patients with PH.